A Retroesophageal Right Subclavian Artery as the Last Branch of the Aortic Arch- In Vivo Case Report - Bahman Jalali Kondori; Elham Rahimian; Mohammad Hossein Asadi; Majid Reza Tahsini (Negah Institute for Scientific Communication, 2014)
Three major arteries normally originate from the aortic arch. Variations of the aortic arch branches are observed in some cases. Rare variation of the aortic arch branches is originated from the retroesophageal right subclavian (RRS) artery as the last branch of the aortic arch. Variation of artery is possibly associated with the variation of the recurrent laryngeal nerve. This research provides an in vivo report of retroesophageal right subclavian artery during examination of the cervical vessels using magnetic resonance angiography (MRA). It is very important to consider the variation of the right subclavian artery during head and neck surgery. Non-invasive techniques such as MRA of cervical arteries can be used in order to examine them.